(untitled) (Annals of Medical Research, 2021)
Aim: This study aims to investigate the effects of vitamin D on adropin and apoptosis in rat kidney tissue in the context of the experimental diabetes model created using streptozotocin (STZ).Material and Methods: 41 male Wistar-albino breed rats of 8-10 weeks were distributed into 5 groups, which consisted of 3 groups with 7 animals each and 2 groups with 10 animals each. No treatments were applied to the control group. The Buffer group was administered with single-dose 0.1 M sodium buffer intraperitoneally (ip). The Vitamin D group was orally administered 200 IU/day vitamin D. The Diabetes group was injected ip with single-dose 50 mg/kg STZ by dissolving the material in 0.1 M sodium buffer.Results: The biochemical and histological investigations revealed similar serum TOS and TAS levels, and TUNEL positivity and Adropin immunoreactivity for the Control, Buffer, and Vitamin D groups. While TOS levels and TUNEL positivity were significantly higher in the Diabetes group compared to the Control group, TAS levels and Adropin immunoreactivity were significantly lower. The TOS levels and TUNEL positivity were significantly reduced in the Diabetes+Vitamin D group compared to the diabetic group, and TAS levels, adropin immunoreactivity were significantly higher. Conclusion: In conclusion; it was determined that experimental diabetes increased TOS and apoptotic cells and decreased TAS and adropin levels in the kidney tissue in experimental diabetes, and that Vitamin D administered as treatment decreased TOS and apoptotic cells and increased TAS and Adropin levels. It was concluded that in order to uncover the role of diabetes in the pathophysiology of its effect on kidney tissue, future studies that consider various experimental diabetes times were necessary.